2017
DOI: 10.5546/aap.2017.eng.556
|View full text |Cite
|
Sign up to set email alerts
|

Erosion of empathy during medical training by gender. A cross-sectional study

Abstract: Introduction. Empathy erosion may be defined as a sudden decline in the levels of empathy that occurs as of the third year of medical school and continues until the fifth year. According to some authors, this process is normal during medical training and may be considered a model of empathic behavior. The objective of this study was to verify whether empathy erosion is a general phenomenon in the schools of medicine included in the study and its relation to gender. Design. Exploratory, cross-sectional study. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
17

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 25 publications
1
15
0
17
Order By: Relevance
“…It is known that empathy has components that are affective-emotional (CC) and cognitive (PT and AUO) (5) . Some authors have suggested that the CC component is difficult to teach, and that it is a product of, or is related to (or both), the moral formation of subjects, family environments, and religiosity (in some cases), among other factors (5)(6)(7)(8)(9)(10) , while the cognitive components (given their nature) are susceptible to being taught (5)(6) . On the other hand (7)(8) , it should be noted that the presence of empathic decline is based on the findings of studies of means of levels of empathy in medical students (11) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that empathy has components that are affective-emotional (CC) and cognitive (PT and AUO) (5) . Some authors have suggested that the CC component is difficult to teach, and that it is a product of, or is related to (or both), the moral formation of subjects, family environments, and religiosity (in some cases), among other factors (5)(6)(7)(8)(9)(10) , while the cognitive components (given their nature) are susceptible to being taught (5)(6) . On the other hand (7)(8) , it should be noted that the presence of empathic decline is based on the findings of studies of means of levels of empathy in medical students (11) .…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors have found evidence that the empathic decline in students does not always occur; this has been found in various health careers (3,(9)(10)(18)(19)(20) . It has been suggested (21) that empathic decline is a particular case of various behaviors of means of empathy throughout courses or years of study, and that there is variability in this behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Al respecto, estudios realizados (5-10) han observado la existencia de la declinación (2). Sin embargo, otros autores han observado variabilidad en la distribución de los valores de empatía a través de los años académicos o cursos (11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionunclassified